Halide salts induced the photodegradation of a fat-burning compound 2, 4-dinitrophenol by iron-montmorillonite. (March 2022) - Peng, Anping; Wang, Yi; Yin, Lichun; Chen, Zeyou; Gu, Cheng
Abstract: Natural montmorillonite clay and anthropogenic organic pollutants frequently coexist in the estuarine environment where freshwater from rivers mixes with saltwater from the ocean. In this environment, the sharply changed aqueous chemistry especially salt content could significantly alter the photochemical behaviors of pollutants. However, this process was rarely investigated. In this study, the photodegradation of a representative anthropogenic weight-loss compound 2, 4-dinitrophenol in the presence of Fe 3+ -montmorillonite and different halide salts was systematically investigated. Results show that 2, 4-dinitrophenol was resistant to photodegradation by Fe 3+ -montmorillonite alone, but the presence of NaCl, NaBr, and sea salts in the system can evoke significant 2, 4-dinitrophenol degradation. The enhancement effect was further elucidated as the replacement reaction between the clay associated Fe 3+ and Na  +  which leads to the release of more interlayer Fe 3+ from montmorillonite, resulting in increased production of high active hydroxyl radicals (˙ OH) that can substantially damage 2, 4-dinitrophenol molecule. In addition, halogen radicals from the reaction of halide ions with ˙ OH were also confirmed to participate in 2, 4-dinitrophenol degradation. Overall, this study implied that the changed salty condition in the estuarine water could induce the rapid transformation of organic pollutants that move from freshwater and have relatively stable photochemical properties. Graphical abstract: Image 1 Highlights: 2, 4-DNP was stable to photodegradation in the presence of Fe 3+ -montmorillonite. Halide salts evoked 2, 4-DNP photodegradation by Fe 3+ -montmorillonite. Replacement reaction between clay associated Fe 3+ and Na  +  released interlayer Fe 3+ . Both .OH and halogen radicals were involved in 2, 4-DNP degradation Salts in estuarine water could induce the rapid degradation of POPs from freshwater.